Sport science: Extending the athlete`s peak performance - Aschwanden, C.; Kopp, B.; Korem, E.; Martin, D.; Smith, S.; Haberstroh, T. (MIT Sloan Sports Analytics Conference 2016, 2016)
Analyzing athletes` performance during games and workout sessions is essential to assess their fitness and skill levels. Sports science is evolving continuously to enable different stakeholders to understand the athlete`s needs and how to get the best performance possible out of them. This panel will discuss how to avoid in-game injuries by analyzing the athlete`s health and techniques, designing the proper workload, correcting techniques, and designing the proper apparel and equipment for each athlete.